EFFECT OF VARIETY AND FERMENTATION ON TARO FLOUR PROXIMATE - Setiawan, Bondan Hary; Cahyani, Dwi Ari (Agripreneur : Jurnal Pertanian Agribisnis, 2023)
Taro flour has higher protein and lower fat than rice flour. Fermentation has an important role in the degradation of complex compounds into simple compounds so that they are easily soluble. The research aims to determine the best taro varieties and determine the effect of fermentation on the taro flour proximate. The research used taro varieties Pratama 1, 2, and 3. Fermentation was carried out using tape yeast for 0 and 72 hours. The experimental design used a randomized design with 6 treatments and 4 replications. Proximate analysis was carried out on taro flour. The analysis results were tested using ANOVA. Next, a follow-up test was used to determine whether there were real differences between the various treatments using the DMRT test (Duncan Multiple Range Test). The research results showed that there were significant differences between treatments. The highest weight of flour of the Pratama 3 variety without fermentation. The highest water content is 9.67% of the Pratama 3 variety without fermentation. Ash content of Pratama 1 variety without fermentation. The highest fat content in Pratama 3 without fermentation. The highest protein content in Pratama 3 with fermentation. The highest carbohydrate content in Pratama 1 with fermentation.